The Impact of Social Media Marketing Components on the Online Consumer Buying Behavior: A Comparative Study between Greek and Finnish consumers - Tsatsou, Dimitra (My University, 2021)
Due to the massive explosion of technology and the Internet boom, every individual can connect, share information and shape relationships. What contributes toward this innovative boost and at the same time creates an effective environment in which a person could function with other people cooperatively, is social media. Through electronic word-of-mouth (e-WOM) and online advertisement, social media brings a new and powerful perspective in shaping consumers' attitudes and behaviours. Thus, this presents marketers with the opportunity to affect consumers purchase decisions through online marketing and social media. Social media marketing offers a connection between the product or service with the consumer while establishing an environment in which every individual can become a part of an influential "social chain-interaction". In this present thesis, the effect of social media marketing mechanisms, namely, e-WOM and online advertisement, is examined on the online Greek and Finnish consumer buying behaviour. A non-probability sampling technique and the convenience sampling method were applied together with the minimum sample size calculation conducted with the log Montel Carlo simulation. "n*(n-Star)" method, in order to establish an appropriate sample strategy and sample size. Two separate online questionnaires with the same questions were distributed across Greek and Finnish participants with a distinct characteristic. They all had an" active social media life". To identify the impact of social media marketing components (e-WOM and online advertisement) on the Greek and Finnish consumers' online buying behaviour, I first go through a detailed data analysis, transformation, and variable selection process. After that stage, two separate multiple regression models are applied to identify the difference between the Greek and Finnish consumers online behaviour. The results suggest that, although both e- WOM and online advertisement significantly affect both the Greek and Finnish online consumer behaviour, e-WOM's impact is far more significant than that of online advertising. These findings indicate that by reading online reviews and watching online advertisements on social media websites, the Greek and Finnish consumers could learn the value of their purchase intentions. Thus, e-WOM communication and online advertisement could be classified as powerful tools of motivation.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business